Structural Topology Optimisation Of Femoral Bone Implant Plate For Biomedical Application (Journal of Namibian Studies : History Politics Culture, 2023)
The design of commercially available fixation plates and the materials used for their fabrication lead to the plates being stiffer than bone. Consequently, commercial plates are prone to induce bone stress shielding. Topology optimization is a process that reveals the most efficient design based on a set of constraints or characteristics, often by removing material from the design. Additive technology is the ideal technique to produce TO components.  For metal fixation plates, the ideal additive manufacturing technologies are selective laser melting (SLM) and electron beam melting (EBM).  In this study, a 4.5mm diameter 8 hole  DCP femoral fixation plate made of Ti–6Al–4V alloy is re-designed using topology optimization to reduce the risk of bone stress shielding. Fixation plate designs were optimized by maximizing stiffness while maintaining the structural integrity. The original plate model was obtained by reverse engineering technique. Altair Inspire topology optimization tool was used in this study for regenerating the optimized design.